CONTINUOUS CASTING OF COPPER ANODES FOR PUTTING OF GALVANIC COAT AT PRODUCTION OF METAL CORD - E. I. Marukovich; V. A. Matochkin; S. R. Chudakov; A. M. Branovitskij; V. A. Dementjev; L. V. Cheshko (Литьë и металлургия)
The investigations of continuous horizontal casting of copper anodes slugs are carried out on the basis of numerical modeling. The dependence of temperature fields of ingot and crystallizer on technological parameters of casting process is established. The technological process and equipping for continuous horizontal casting of bar of copper and alloys on its basis in crystallizer with graphite insert are developed.